Functional Analysis of Genes Encoding Juvenile Hormone Receptor Met and Transcription Factor Kr-h1 in the Reproductive Capacity of Coccinella septempunctata Males - Ying Cheng; Yuhang Zhou; Cao Li (Insects)
This study focuses on the regulatory effects of genes encoding the juvenile hormone (JH) receptor methoprene-tolerant (Met) and transcription factor krüppel homolog 1 (Kr-h1) on the reproductive capacity of Coccinella septempunctata male adults. Met and Kr-h1 expression levels were analyzed in males fed on artificial diets with and without JH by quantitative real-time PCR, and the effects of Met and Kr-h1 on male reproduction were analyzed by RNA interference technology. Met transcription levels in 5- and 10-day-old males fed with a JH-supplemented diet were lower than those without JH. Kr-h1 expression in 5-day-old adult males was lower in diets lacking JH but was higher in 10-day-old males fed on a diet lacking JH. There were no significant differences in the testes sizes of male ladybugs injected with Met-dsRNA when compared to GFP-dsRNA; however, the testis volume of ladybugs injected with Kr-h1-dsRNA was smaller than those injected with GFP-dsRNA. After males were injected with Met-dsRNA and Kr-h1-dsRNA, the mean egg production by females decreased by 12.75% and 23.10%, respectively, at 20 d postinjection. Our results show that Met and Kr-h1 have important roles in regulating reproduction by directly affecting testes development in males and egg production in females.